2010
DOI: 10.1007/s13167-010-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion and work: prevention of shift work disorders in companies

Abstract: Workplace health promotion is a strategy to improve the health and well-being of people at work. The measures aim at the personal, organisational and work environment. Shift work is one of many reasons provoking increased job stress. According to worldwide epidemiological data, up to 30% of the working population are employed in shifts. Taking into consideration that shift work causes a large number of somatic and psychiatric diseases which bear considerable negative consequences for the health status and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses. For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services (Barger et al., ; Rajaratnam et al., ; Richter, Acker, Scholz, & Niklewski, . Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses. For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services (Barger et al., ; Rajaratnam et al., ; Richter, Acker, Scholz, & Niklewski, . Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study identified sleep disturbances as a partial mediator in the association between work-family conflict and depressive symptoms among nurses. Future interventions to promote healthy sleep practices should be evaluated for their effectiveness in addressing the impact of work-family conflict on the mental health of nurses.Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses.For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services(Barger et al, 2016;Rajaratnam et al, 2011;Richter, Acker, Scholz, & Niklewski, 2010. Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
mentioning
confidence: 99%
“…(Beermann 2010;Knauth 1993;Wedderburn 2000). Derartige Gestaltungshinweise sind der gesundheitlichen Vorsorge dienlich, zumal sie nicht allein auf Verhaltensänderungen von Beschäftig-ten vertrauen (Richter et al 2010) …”
Section: Resümeeunclassified
“…Therefore, health promotion is becoming an important strategy of many companies. The effort is to integrate targeted programs to change workers lifestyles and thus prevent the negative influence of risk factors (Richter et al, 2010). There is a growing need to integrate and implement workshops of healthy lifestyle in the healthcare sector/organizations.…”
Section: Discussionmentioning
confidence: 99%